Transfer and referral of a practicing nurse to tasks related to preventing, counteracting, and combating the COVID -19 epidemic - Karkowska, Dorota (Nursing Problems / Problemy Pielęgniarstwa, 2020)
The article was prepared on the basis of an analysis of current legal acts and case law of common courts, in particular the Supreme Court. Based on the analysis, the conclusion is that the possibility of transferring or referring a nurse to work in combating the effects of the COVID-19 epidemic depends on the form of employment and the mode of performed activity. Nurses with an employee status who are transferred to perform tasks other than the ones specified in the employment contract, by way of an employer’s official order issued in accordance with Article 42 Paragraph 4 of the Labour Code, are not subject to the exclusion due to the care of a minor child, a chronically ill person, or due to the age of 60 years or more. However, according to the Labour Code, women will be subject to such an exemption during pregnancy or nursing a baby. The possibility of obliging a nurse employed on the basis of a civil law contract to take care of persons with suspected coronavirus infection is decided by the parties by making a declaration of will in the contract. Regardless of the current form of practicing the profession, a nurse may be referred to work in combating an epidemic, including the care of persons with suspected coronavirus infection, through the administrative and legal mode, based on the decision of the voivode or the minister of health.